2012
DOI: 10.1007/s11803-012-0141-1
|View full text |Cite
|
Sign up to set email alerts
|

Comparative efficiency analysis of different nonlinear modelling strategies to simulate the biaxial response of RC columns

Abstract: Abstract:The performance of different nonlinear modelling strategies to simulate the response of RC columns subjected to axial load combined with cyclic biaxial horizontal loading is compared. The models studied are classifi ed into two categories according to the nonlinearity distribution assumed in the elements: lumped-plasticity and distributed inelasticity. For this study, results of tests on 24 columns subjected to cyclic uniaxial and biaxial lateral displacements were numerically reproduced. The analyses… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
17
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 58 publications
(18 citation statements)
references
References 26 publications
1
17
0
Order By: Relevance
“…For a short-period shearcritical structure, the global response can be largely different depending on the adopted numerical model. Rodrigues et al (2012) made a comparison between lumped plasticity and distributed inelasticity. The results of experimental and numerically analysis of 24 columns show that the global envelope response is satisfactorily represented with the three modeling strategies, but significant differences were found in the strength degradation for higher drift demands and energy dissipation.…”
Section: Introductionmentioning
confidence: 99%
“…For a short-period shearcritical structure, the global response can be largely different depending on the adopted numerical model. Rodrigues et al (2012) made a comparison between lumped plasticity and distributed inelasticity. The results of experimental and numerically analysis of 24 columns show that the global envelope response is satisfactorily represented with the three modeling strategies, but significant differences were found in the strength degradation for higher drift demands and energy dissipation.…”
Section: Introductionmentioning
confidence: 99%
“…Deierlein et al summarized the main features of five types of frame elements and provided a general modeling guideline. Rodrigues et al compared the efficiency of three fiber models to represent the biaxial behavior of RC columns. In addition to these, there is a large body of studies on numerical modeling of RC elements.…”
Section: Introductionmentioning
confidence: 99%
“…This decision was based on the reports provided by Priestley and Park [27], Paulay and Priestley [28] and by other authors who have concluded from experimental evidence that the plastic hinge length is not strongly affected by two-dimensional loading [29]. The modeling assumptions adopted for the beams and columns were based on the conclusions of the work developed by Rodrigues et al [30], in which they studied the biaxial flexural behavior of RC columns. For the concrete modeling, the uniaxial material model based on the Mander et al [31] and Madas [32] uniaxial models was adopted.…”
Section: Numerical Modeling Strategiesmentioning
confidence: 99%